Synthesis of N-Glycolylneuraminic Acid (Neu5Gc) and Its Glycosides - Kooner, Anoopjit Singh; Yu, Hai; Chen, Xi (Frontiers in Immunology, 2019)
Sialic acids constitute a family of negatively charged structurally diverse monosaccharides that are commonly presented on the termini of glycans in higher animals and some microorganisms. In addition to N-acetylneuraminic acid (Neu5Ac), N-glycolyl neuraminic acid (Neu5Gc) is among the most common sialic acid forms in nature. Humans cells do not have the ability to synthesize Neu5Gc although Neu5Gc-containing glycoconjugates have been found on human cancer cells and in various human tissues. In addition to Neu5Gc, more than 20 Neu5Gc derivatives have been found in nature. To explore the biological roles of Neu5Gc and its naturally occurring derivatives as well as the corresponding glycans and glycoconjugates, various chemical and enzymatic synthetic methods have been developed to obtain a vast array of Neu5Gc and derivative-containing glycosides. Here we provide an overview on various synthetic methods developed. Among these, highly efficient one-pot multienzyme (OPME) sialylation systems have been proven as a powerful synthetic strategy.